The application research of Sunken hidden anchor bolt foundation in 1000kV UHV substation. Issue 3 (July 2021) - Fu, Yanwei
Abstract: This paper mainly deals with the efficient utilization of the land occupied by the permanent foundation of temporary buildings. The main transformer maintenance workshop is set up in the 1000kV UHV substation for the main transformer fault phase maintenance. The main transformer maintenance workshop is of prefabricated steel structure. During the substation operation, only the permanent foundation is retained. Once the main transformer needs maintenance, the maintenance party shall bring steel structure components to the site for workshop construction. After the overhaul, the overhaul party will remove the steel structure and take it away for the site or other stations to continue to use, while the permanent foundation will continue to be retained.